IMPLEMENTASI PROGRAM SHELTER ANAK TERHADAP KESEJAHTERAAN HIDUP ANAK RUMAH SINGGAH ANAK JALANAN KOMUNITAS PEDULI ANAK (KOPA) - Rebecca Ruth Marpaung; Putri, Malida (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The kids the very commonly encountered in big cities, often operating in to centers around the square, large market, intersection red light, etc. The handling of street children is very important consideration, in addition to them to get their rights and welfare as set out in the constitution 1945. This research aims to review the implementation of the shelters for the welfare of the child life in a community care children ( Kopa ) Medan. This study used research with a qualitative approach descriptive. Based on interviews, observation and dokumentansi study that researchers did in the community care children ( Kopa ) Medan three aspects that have not been entirely good, in a program like the low achievement with clear purpose, the absence of budget. While in terms of implementing organizations have structured but there is no consistency from program implementers. Then at a target or the target group that it is clear and precise carried out even though the purpose of the program was not as a maximum.